Myxofibroma of the maxilla, current concepts, and differential diagnosis - Abdulkadir Burak Cankaya; Mehmet Ali Erdem; Bilge Bilgic; Deniz Firat (Elsevier, 2017)
Odontogenic myxomas represent a small portion of all odontogenic tumors. A myxoma of the bone is a rare lesion that occurs almost exclusively in the jaws. An odontogenic myxoma has a variable clinical and radiological appearance, and it should be considered in the differential diagnosis of radiolucent and mixed radiolucentâradiopaque lesions of both jaws in all age groups. Myxomas consist of an accumulation of mucoid ground substance with little collagen, the amount of which determines whether it is called a myxofibroma. This paper presents the case of a 39-year-old male with a solid whitish red, nonulcerative, nontender expansion of both the buccal and palatal sides of the right upper alveolar bone. Results of a radiological examination revealed a unilocular radiolucency with cortical expansion and displacement of both the right upper second premolar and the first molar. The lesion was totally excised, and the histopathological examination showed a myxofibroma. Healing was uneventful, and there was no recurrence 12 months after surgical excision. Complete removal of the tumor, leaving no remnants attached to the soft tissue or bone, should be considered because of the well-known potential of myxofibromas to recur. Keywords: maxilla, myxofibroma, odontogenic tumor